Designing an Educational Comic on Nationalism Based on the Historical Events of Sanga Sanga in East Kalimantan - Ramadhan S. Pernyata; Royke Vincentius (Jurnal Indonesia Sosial Sains, 2026)
The design of this comic, set against the backdrop of the historic Sanga Sanga struggle in East Kalimantan, is part of a strategic effort to provide contextual and engaging educational media for the younger generation. This comic is designed to enhance students' understanding of local history while instilling nationalistic values through a communicative visual and narrative approach. The design process employed a descriptive qualitative method with a practice-based model. Research. The design stage begins with identifying the objectives and target audience, followed by field observations, collecting historical data and location documentation, and conducting literature studies related to the Palagan Sanga Sanga incident. January 27, 1947. The results of this research were then transformed into a story script and dialogue relevant to young readers, followed by the development of representative character designs and visual styles. The next process included storyboarding, panel layouts, illustrations and coloring, as well as graphic elements such as typography and narrative text. The final stage, a limited trial with students and teachers, was conducted to obtain feedback on readability, visual appeal, and the effectiveness of the message conveyed. Through this approach, comics not only become a means of preserving local history, but also a learning medium capable of connecting the younger generation with the values of struggle, patriotism, and love of the homeland in a more relevant and meaningful way